Infiltrating CD8(+) T lymphocytes, natural killer cells, and expression of IL-10 and TGF-beta 1 in chemically induced neoplasms in male Wistar rats - Spinardi-Barbisan, ALT; Barbisan, Luis Fernando [UNESP]; de Camargo, JLV; Rodrigues, MAM (Taylor & Francis Inc, 2004)
The present study aimed to estimate the number of CD8(+) T and natural killer (NK) infiltrating cells and the expression of interleukin-10 (IL-10) and transforming growth factor beta 1 (TGF-beta1) in chemically induced neoplasms in an initiation-promotion bioassay for carcinogenesis. Male Wistar rats were treated with N-nitrosodiethylamine, N-methyl-N-nitrosourea, N-butyl-N-(4-hydroxybutyl) nitrosamine, dihydroxy-di-N-propylnitrosamine, and 1,2-dimethylhydrazine for 4 weeks. Two groups were subsequently exposed through diet to phenobarbital (0.05%) or 2-acetylaminofluorene (0.01%) for 25 weeks. An untreated group was used as a control. Immune cells and cytokines were immunohistochemically evaluated in neoplasms and in surrounding normal tissues at the liver, kidneys, lung, and small and large intestines. When compared to the respective normal tissues, an increased number of NK cells was verified infiltrating the colon, lung, and kidney neoplasms, while the number of CD8+ T cells decreased in the intestine and lung neoplasms. Expression of IL-10 was found mainly in kidney tumors. TGF-beta1 was expressed mainly in the liver and kidneys tumors. The results indicate that the differential occurrence of immune cells between neoplastic and normal tissues could be dependent upon tumor microenvironment.
Keywords: initiation-promotion; neoplasia; cytokines; tumor-infiltrating lymphocytes; natural killer cells